Systemic Functional Linguistics as an Extension of Prague School in Competency-Based Language Learnng and Literacy Education - Sugeng Purwanto (Dinamika Bahasa dan Budaya, 2015)
This artile presents Systemic Functional Linguistics as an extension of Prague School in competency-based language learning and literacy education. Unlike  Bloomfield who considers that utterances are element   (-emes) and  Chomsky who considers utterances as rules, the Prague School of Linguistics considers utterances as function (motor). Utterances are means of expressing meanings which, by Halliday, are described in three domains: Ideational, interpersonal and textual. Most educational practitioners have taken up Halliday’s principles in developing competency-based language learning and literacy education. Key words: Prague School, Systemic Functional Linguistics, ompetency-based language learning, literacy education.